Food Security TEP - Supporting sustainable intensification of food production from Space. Issue 1 (June 2020) - Muerth, M; Migdall, S; Hodrius, M; Niggemann, F; Holzapfel, M; Bach, H; Gilliams, S; van Roey, T; Cuomo, A; Harwood, P; Pace, N; San Miguel Sanchez, I; et al.
Abstract: The Food Security Thematic Exploitation Platform (TEP) supported by ESA is a cloud platform for the extraction of information from EO data for services in the food security sector. To respond to the needs of its large user community, the platform is developed in an agile mode in close coordination with its users. Thereby it targets to foster smart, data-intensive agricultural and aquacultural applications in the scientific, private and public domain. During the first two years of platform development, the Food Security TEP project team has deployed a number of service pilot applications. This paper presents those focusing on the support of micro-financing and irrigation for African farmers and on supporting coastal aquaculture development in Africa.